A mechanistic insight into the anticancer potentials of resveratrol: Current perspectives - Bhuia, Md. Shimul; Chowdhury, Raihan; Akter, Mst. Asma; Ali, Md. Arman; Afroz, Meher; Akbor, Md. Showkot; Sonia, Fatema Akter; Mubarak, Mohammad S.; Islam, Muhammad Torequl (Phytotherapy research, 2024)
Resveratrol is a widely recognized polyphenolic phytochemical found in various plants and their fruits, such as peanuts, grapes, and berry fruits. It is renowned for its several health advantages. The phytochemical is well known for its anticancer properties, and a substantial amount of clinical evidence has also established its promise as a chemotherapeutic agent. This study focuses on assessing the anticancer properties of resveratrol and gaining insight into the underlying molecular mechanisms. It also evaluates the biopharmaceutical, toxicological characteristics, and clinical utilization of resveratrol to determine its suitability for further development as a reliable anticancer agent. Therefore, the information about preclinical and clinical studies was collected from different electronic databases up‐to‐date (2018–2023). Findings from this study revealed that resveratrol has potent therapeutic benefits against various cancers involving different molecular mechanisms, such as induction of oxidative stress, cytotoxicity, inhibition of cell migration and invasion, autophagy, arresting of the S phase of the cell cycle, apoptotic, anti‐angiogenic, and antiproliferative effects by regulating different molecular pathways including PI3K/AKT, p38/MAPK/ERK, NGFR‐AMPK‐mTOR, and so on. However, the compound has poor oral bioavailability due to reduced absorption; this limitation is overcome by applying nanotechnology (nanoformulation of resveratrol). Clinical application also showed therapeutic benefits in several types of cancer with no serious adverse effects. We suggest additional extensive studies to further check the efficacy, safety, and long‐term hazards. This could involve a larger number of clinical samples to establish the compound as a reliable drug in the treatment of cancer. Therapeutic potential of resveratrol on cancer and molecular mechanims based on different preclinical and clinical assessments.